ALLELOPATHIC EFFECT OF Senna obtusifolia ON SEED GERMINATION OF VEGETABLES Lactuca sativa AND Beta vulgaris - de Sousa, Ana Paula Martins; de Sá, Maria Eduarda Souza; Ramos, Gustavo Pires dos S.; de Sousa, Francisca Martins; Dias, Maria Vitória Gomes; de Sousa, Verônica Borges; Costa, Eduardo William de Araújo (Seven Editora, 2025)
Allelopathy refers to the effects that one organism can cause on another directly or indirectly, and can favor or suppress everything from seed germination to seedling development. The allelopathic action is specific, that is, each plant, both living and decomposing, exerts inhibition only on certain species. These compounds, produced in various parts of plants, such as leaves and roots, can be released by exudation, volatilization, leaching or decomposition of waste. Its effects are varied, including inhibition of germination, impaired growth, and, in extreme cases, death of recipient plants. Although allelopathy can have positive or negative effects, its impact is specific depending on the plants involved. In horticulture, recent studies demonstrate the potential allelopathic effects on crops such as lettuce and sugar beets. For example, extracts of Nicotiana tabacum and Eucalyptus grandis have shown inhibitory effects on the germination of lettuce and broccoli seeds. Species such as Senna obtusifolia, a weed common in several agricultural areas, stand out for their potential to inhibit crop development due to the release of allelochemicals. Studies such as the impact of Senna obtusifolia on vegetables are essential to better understand these mechanisms and develop more sustainable agricultural practices, promoting greater productivity and cost reduction in agroecosystems. DOI: https://doi.org/10.56238/sevened2024.037-163